Infestation by the epibiont Octolasmis lowei in a portunid crab assemblage from a subtropical coast - Silva-inácio, Lylian Marcia Da; Machado, Glauco Barreto De Oliveira; Fortuna, Monique D'assunção; Sanches, Fabio Henrique Carretero; Costa, Tânia Marcia (Sociedade Brasileira de Carcinologia, 2016)
ABSTRACT We investigated the infestation by Octolasmis lowei Darwin, 1851 in branchial chambers of the portunid Achelous spinimanus (Latreille, 1819), Arenaeus cribrarius (Lamarck, 1818), Callinectes danae Smith, 1869, and Callinectes ornatus Ordway, 1863. We evaluated how infestation is related to host maturity, molt stage, carapace width and sex. The infestation probability increases with host carapace width, and infested crabs were more likely to be adults in intermolt stage. Infestation prevalence did not differ between sexes, except for C. ornatus, in which females had higher infestation than males. Infestation intensity was higher for males than females in A. cribrarius and A. spinimanus, while C. ornatus showed an opposite pattern. Association of O. lowei with portunid seems to be tightly related to the biological traits of its host. Some of these traits, such as host size, maturity and molt stage, are likely to affect infestation in a similar way for all host species, while the effect of other traits, such as sex identity, seems to vary among hosts. We suggest a deeper understanding of the factors driving host use by generalist epibionts such as O. lowei depends on investigating their occurrence on a variety of potential hosts, as well as performing manipulative studies to evaluate the factors driving host preferences by this epibiont.
Keywords: Decapods; epibiosis; infestation patterns; stalked barnacle